A case study in support of closure of bow shock current through the ionosphere utilizing multi-point observations and simulation - Dredger, Pauline M.; Lopez, Ramon E.; Hamrin, Maria (Frontiers in Astronomy and Space Sciences, 2023)
On the bow shock in front of Earth’s magnetosphere flows a current due to the curl of the interplanetary magnetic field across the shock. The closure of this current remains uncertain; it is unknown whether the bow shock current closes with the Chapman-Ferraro current system on the magnetopause, along magnetic field lines into the ionosphere, through the magnetosheath, or some combination thereof. We present simultaneous observations from MMS, AMPERE, and DMSP during a period of strong B_y, weakly negative B_z, and very small B_x. This IMF orientation should lead to a bow shock current flowing mostly south to north on the shock. AMPERE shows a current poleward of the Region 1 and Region 2 Birkeland currents flowing into the northern polar cap and out of the south, the correct polarity for bow shock current to be closing along open field lines. A southern DMSP F18 flyover confirms that this current is poleward of the convection reversal boundary. Additionally, we investigate the bow shock current closure for the above-mentioned solar wind conditions using an MHD simulation of the event. We compare the magnitude of the modeled bow shock current due to the IMF B_y component to the magnitude of the modeled high-latitude current that corresponds to the real current observed in AMPERE and by DMSP. In the simulation, the current poleward of the Region 1 currents is about 37% as large as the bow shock I_z in the northern ionosphere and 60% in the south. We conclude that the evidence points to at least a partial closure of the bow shock current through the ionosphere.